PENGARUH BERMAIN KREATIF TERHADAP PERKEMBANGAN EMOSI ANAK KELOMPOK B PAUD SINAR HARAPAN DESA AIR RUSA, CURUP - Aprilianti Ningsih; Sri Saparahayuningsih; Wembrayarli Wembrayarli (Universitas Bengkulu, 2017)
The problem in this research is there was any difference of emotional development using creative play method. The purpose of this research was to know the difference of emotional development using creative play method. The method used was quasi experiments. Subjects in this study were children in group B PAUD Sinar Harapan Air Rusa Village. Data collection techniques used was observation. Analysing data in this research used statistical analysis technique, prerequisite test analysis and hypothesis test (test of t-test). The result of this research show that there were differences between emotional behavior in Flubbyjelly experiment group and Fingerpainting experiment group, as proved by the results of t-test calculations obtained tcount it turns out that its value was greater than ttable. Then Ha accepted and Ho rejected, so there was influence of playing Flubbyjelly against the development of children emotions. Through this research, expected that it can be applied on other developments such as motor, cognitive and social child.